Beginning teachers' knowledge-in-practice of multicultural science education. Issue 3 (27th June 2020) - Kye, Hannah
Abstract : Purpose: This paper aims to describe the results of a qualitative case study of three beginning elementary teachers' knowledge-in-practice of multicultural science education. Design/methodology/approach: Data included interviews, focus group discussions, audio-recorded lessons and daily field notes through the course of a month-long summer science program. Data were coded deductively using a framework of receptivity and resistance, and then coded inductively to determine themes within each category of data. Findings: Analysis revealed three key elements of teachers' knowledge-in-practice: positive perceptions of teaching for social justice, practices that overlooked students' perspectives and practices that discounted race and culture in science. Originality/value: Insights from this case study respond to the well-documented need to address the gap between knowledge and practice in multicultural science education by revealing potential roadblocks and guideposts useful for bridging this gap.